The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003 IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2003. Proceedings.
DOI: 10.1109/cvpr.2003.1211429
|View full text |Cite
|
Sign up to set email alerts
|

Occupant classification system for automotive airbag suppression

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 6 publications
1
30
1
Order By: Relevance
“…The camera has no absolute calibration and is subject to considerable drift in both gain and offset with temperature. It does have a mechanism for correcting per pixel gain variation, which employs a shutter that momentarily closes in front of the focal plane array every few minutes [13]. Miniaturization and cost reduction is moving at a rapid pace in LWIR cameras, with roughly a four-fold decrease in both size and price in the last two years.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The camera has no absolute calibration and is subject to considerable drift in both gain and offset with temperature. It does have a mechanism for correcting per pixel gain variation, which employs a shutter that momentarily closes in front of the focal plane array every few minutes [13]. Miniaturization and cost reduction is moving at a rapid pace in LWIR cameras, with roughly a four-fold decrease in both size and price in the last two years.…”
Section: Related Studiesmentioning
confidence: 99%
“…Farmer and Jain [13] presented work on an occupant classification system that addresses the static suppression requirement of the NHTSA standard by a system that is able to discern between four categories of occupants with high detection rates. The static suppression requirement specifies occupant types that, when present in the passenger seat, the airbag system must automatically suppress deployment [1].…”
Section: Related Studiesmentioning
confidence: 99%
“…A system of sensors can detect who is currently in the passenger/driver seat by utilizing, for example, weight or posture and automatically adjusting the vehicle to personal needs [140][141][142].…”
Section: Occupant Classification Systems (Ocs)mentioning
confidence: 99%
“…Since it has been shown that there is no universally best classifier, we decided to initially apply the k-nearest neighbour based on its simplicity of implementation [28]. We used a modification of the k-nearest neighbor classifier, which computes the average distance of the test sample to the k-nearest training samples in each class, and then uses the average of this distance as the classification distance [1]. This distance-based k-nearest neighbor classifier is related to the nearest mean classifier, where we compute a pruned mean for each class based on the sorted distances of the training samples, however, we select the top k from each class rather than the top k of the combined set of classes.…”
Section: Classification Of Blob Combinationsmentioning
confidence: 99%
“…We will demonstrate our proposed framework on a vision-based smart airbag application, where the airbag is automatically disabled if the occupant is an infant [1]. The smart airbag application can be defined as a 2-class classification problem: (i) infant (referred to as class 1), (ii) adult (referred to as class 2), where the airbag is suppressed when the passenger is an infant.…”
Section: Introductionmentioning
confidence: 99%